2023
DOI: 10.3390/diagnostics13071253
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Approach to the Diagnosis and Prediction of HCC Using CK19 and Glypican 3 Biomarkers

Abstract: Various statistical models predict the probability of developing hepatocellular carcinoma (HCC) in patients with cirrhosis, with GALAD being one of the most extensively studied scores. Biomarkers like alpha-fetoprotein (AFP), AFP-L3, and des-g-carboxyprothrombin (DCP) are widely used alone or in conjunction with ultrasound to screen for HCC. Our study aimed to compare the effectiveness of Cytokeratin 19 (CK19) and Glypican-3 (GPC3) as standalone biomarkers and in a statistical model to predict the likelihood o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In an Italy cohort, the diagnostic efficacy of GALAD (AUC: 0.98) was better than the triple‐biomarker combination only (AUC: 0.95) 92 . Studies from different groups indicated that the AUC of the GALAD for HCC detection were all above 0.95 93–95 …”
Section: The Algorithms For the Combined Application Of The Triple‐bi...mentioning
confidence: 95%
See 1 more Smart Citation
“…In an Italy cohort, the diagnostic efficacy of GALAD (AUC: 0.98) was better than the triple‐biomarker combination only (AUC: 0.95) 92 . Studies from different groups indicated that the AUC of the GALAD for HCC detection were all above 0.95 93–95 …”
Section: The Algorithms For the Combined Application Of The Triple‐bi...mentioning
confidence: 95%
“… 92 Studies from different groups indicated that the AUC of the GALAD for HCC detection were all above 0.95. 93 , 94 , 95 …”
Section: The Algorithms For the Combined Application Of The Triple‐bi...mentioning
confidence: 99%